Experiences, coping strategies, and family support received by male and female UP basketball team players after UAAP competition loss - Asis, Ina Sofia B.; Policarpio, Hannah C.; Tongson, Excelsa C. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT The research looked into the experiences, coping strategies, and family support received by the U.P. Basketball Team players after a competition loss in the University Athletic Association of the Philippines (UAAP) tournament. Qualitative research approach was used in this study. Fifteen (15) male and fifteen (15) female players were randomly selected for a one-on-one interview and thematic analysis was used to process the data gathered. Results showed that both male and female players undergone emotional-related experiences after a UAAP competition loss. To cope with this, both male and female players used self-motivation. They also received support from their family which were mostly words of encouragement and the mere act of sharing their experiences with them. Males were also more inclined to their fathers while females to their mothers. Future studies may look into the kind of support student-athletes receive from other people such as their friends, significant others, and coaches.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Loss (Psychology); College athletes -- Philippines; University of the Philippines -- Basketball players